Estimation abilities of large numerosities in Kindergartners - Mejias, Sandrine; Schiltz, Christine (Frontiers in Psychology, 2013)
The approximate number system (ANS) is thought to be a building block for the elaboration of formal mathematics. However, little is known about how this core system develops and if it can be influenced by external factors at a young age (before the child enters formal numeracy education). The purpose of this study was to examine numerical magnitude representations of 5 to 6 year old children at 2 different moments of Kindergarten considering children’s early number competence as well as schools’ socio-economic index (SEI). This study investigated estimation abilities of large numerosities using symbolic and non-symbolic output formats (8 to 64). In addition, we assessed symbolic and non-symbolic early number competence (1 to 12) at the end of the 2nd (N = 42) and the 3rd (N = 32) kindergarten grade. By letting children freely produce estimates we observed surprising estimation abilities at a very young age (from 5 year on) extending far beyond children’s symbolic explicit knowledge. Moreover, the time of testing has an impact on the ANS accuracy since 3rd kindergarteners were more precise in both estimation tasks. Additionally, children who presented better exact symbolic knowledge were also those with the most refined ANS. However, this was true only for 3rd kindergarteners who were a few months from receiving math instructions. In a similar vein, higher SEI positively impacted only the oldest children’s estimation abilities whereas it played a role for exact early number competences already in 2nd and 3rd graders. Our results support the view that approximate numerical representations are linked to exact number competence in young children before the start of formal math education and might thus serve as building blocks for mathematical knowledge. Since this core number system was also sensitive to external components such as the SEI this implies that it can most probably be targeted and refined through specific educational strategies from preschool on.